A Circular Bioeconomy with Biobased Products from CO2 Sequestration. Issue 6 (June 2016) - Venkata Mohan, S.; Modestra, J. Annie; Amulya, K.; Butti, Sai Kishore; Velvizhi, G.
Abstract : The unprecedented climate change influenced by elevated concentrations of CO2 has compelled the research world to focus on CO2 sequestration. Although existing natural and anthropogenic CO2 sinks have proven valuable, their ability to further assimilate CO2 is now questioned. Thus, we highlight here the importance of biological sequestration methods as alternate and viable routes for mitigating climate change while simultaneously synthesizing value-added products that could sustainably fuel the circular bioeconomy. Four conceptual models for CO2 biosequestration and the synthesis of biobased products, as well as an integrated CO2 biorefinery model, are proposed. Optimizing and implementing this biorefinery model might overcome the limitations of existing sequestration methods and could help realign the carbon balance. Trends: Conceptualized biobased CO2 sequestration models yield high-value biobased products and platform chemicals. The imbalanced carbon flux in the environmental matrix can be rebalanced by adopting biological sequestration methods. CO2 -based high-value bioproducts can fuel our vision of a circular bioeconomy. An integrated hybrid biorefinery model in which carbon flows in a closed loop might prove to be a sustainable and promising research direction. Probing the potential of diverse microbial taxa, including both photosynthetic and nonphotosynthetic organisms, to assimilate CO2 through different metabolic pathways might help to maintain ecologically friendly carbon footprints.